Civil strife and Education of Children A Study of Districts Affected by Left wing Extremism - Chugh, Sunita (JOURNAL OF INDIAN EDUCATION, 2014)
Activities of left wing extremists called naxalites are adversely affecting the functioning of school system in several parts of the country. The problem is found to be particularly severe in a few states like Andhra Padesh, Bihar, Jharkhand, Chhattisgarh, Madhya Pradesh, Maharashtra, Orissa and West Bengal. In all, about 83 districts were identified as affected by civil strife with 35 of these as severely affected. These districts are predominantly inhabited by population of different tribal groups and are mostly covered with forest that provides natural protection to armed groups. The security forces have occupied several schools either partially or fully driving out teachers and students disturbing the function of schooling system in these areas. The ever presence of large contingent security personnel and ever present threat of violence breaking any point of time has put off children particularly girl child from schools.